Evaluasi Implementasi Tata Kelola Teknologi Informasi Berdasarkan Framework CobIT - Rina Elina (CV. Syntax Corporation Indonesia, 2021)
Information technology support can improve the company's capabilities in added value creation, the best quality of service and efficient and effective implementation of the company's operations. Therefore, structured information technology governance ranging from planning to supervision so that the existence of information technology is able to support the company's success in achieving its business goals and ensure efficiency, cost reduction and increased control over Information Technology investment. PT. Krakatau Steel (Persero), Tbk has implemented information technology governance and has conducted an audit using the CobIT framework. This research aims to evaluate the implementation of Technology Governance in PT. Krakatau Steel (Persero), Tbk is seen in the Framework of CobIT with qualitative descriptive data analysis methods. This research was conducted by observation and by conducting open interviews to related parties in the BE, IT / IS and MS. Secondary data in the form of CobIT mapping results ranging from business objectives to IT processes from the BE, IT / IS and MS divisions then continued by the author by conducting an AUDIT of IT processing to obtain primary data. The results showed that there were still 6 (six) weaknesses that had not been done by the BE, IT / IS and MS divisions in IT Process PO2, PO5, PO8, PO9, PO10 and DS6 and given several recommendations for improvement